2019
DOI: 10.1111/hepr.13327
|View full text |Cite
|
Sign up to set email alerts
|

Albumin–Indocyanine Green Evaluation (ALICE) grade combined with portal hypertension to predict post‐hepatectomy liver failure

Abstract: Aim The aim of this study was to evaluate the role of liver function factors in predicting a postoperative large‐volume ascites (LA) and post‐hepatectomy liver failure (PHLF). Methods We included 1025 consecutive patients undergoing hepatectomy for hepatocellular carcinoma between 2002 and 2014. Univariate and multivariate analyses were carried out to evaluate the role of each factor of liver function in predicting LA and PHLF. Factors included the presence of portal hypertension (PH), extent of resection, Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…In the present case, we reduced HVPG to > 10 mmHg before hepatic resection. Sirata et al reported that in the ALICE grade 2 group, patients with PH showed high incidence of large-volume ascites and post-hepatectomy liver failure for HCC [11]. In addition, sectoriectomy or more was also a risk factor to large-volume ascites and liver failure in patients with ALICE grade 2 and PH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present case, we reduced HVPG to > 10 mmHg before hepatic resection. Sirata et al reported that in the ALICE grade 2 group, patients with PH showed high incidence of large-volume ascites and post-hepatectomy liver failure for HCC [11]. In addition, sectoriectomy or more was also a risk factor to large-volume ascites and liver failure in patients with ALICE grade 2 and PH.…”
Section: Discussionmentioning
confidence: 99%
“…The ALICE score was calculated by means of the following formula: 0.663 × log10 ICGR15 − 0.718 × albumin (g/dl) [12]. The ALICE grade was stratified as follows: ALICE grade 1, linear predictor value of < − 2.20; ALICE grade 2a, linear predictor value of − 2.20 to − 1.88; ALICE grade 2b, linear predictor value of − 1.88 to − 1.39; and ALICE grade 3, linear predictor value of > − 1.39 [11,12]. The ICGR15 has been widely used in the field of hepatobiliary surgery in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…10 Most recently, Shirata et al suggested in their study that the ALICE score was the strongest predictor for large-volume ascites and liver failure after hepatectomy. 12 In the present study, we evaluated these new systems in terms of their homogeneity, discriminatory ability, AIC, and AUROC regarding overall survival. This method is similar to that used in previous studies comparing the staging of digestive cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The ALICE score is calculated, including the indocyanine green retention rate at 15 min (ICG R15) and albumin, using the following formula: 0.663 × log 10 ICG R15 (%) – 0.0718 × albumin (g/L), and also divided into three grades by the ALICE grade (cut‐off values of grades 1/2 and 2/3 were −2.20 and −1.39, respectively). To the best of our knowledge, the usefulness of the ALICE grade system has not been substantially considered, and only a few articles have compared these two grading systems …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation